Frequency of Depression in Patients of Type 2 Diabetes Mellitus - Sana, Muhammad Ahsan; Kashif, Nouman; Azam, Khalid (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency of depression and associated risk factors in patients with type 2 diabetes mellitus.Study Design: Cross-sectional study.Place and Duration of Study: Department of General Medicine, Combined Military Hospital, Lahore Pakistan, from Jan to Apr 2020.Methodology: One hundred and two patients with type 2 diabetes mellitus visiting OPD were enrolled in the study.Depression was assessed using the Urdu version of Beck’s Depression Inventory. In addition, smoking status, history of hypertension, duration of diabetes, drug history and HbA1c levels were recorded.Results: Of 102 participants 57(55.9%) were males and 45(44.1%) were females. 43(42.2%) showed depression, 28(27.5%) had mild depression, 11(10.8%) had moderate depression and 4(3.9%) had severe depression. 87(85.3%) had poor glycemic control.There was a significant relationship between the duration of diabetes mellitus and depression (r=0.238 p=0.016). The risk of depression was more in patients with hypertension (OR: 2.206, CI: 0.981–4.947, p=0.054), smokers (OR: 2.191, CI: 0.796 – 6.031,p=0.124) and patients on insulin therapy (OR: 1.891, CI: 0.769 – 4.647, p=0.162).Conclusion: A significant number of patients with type 2 diabetes mellitus have depression. Concomitant hypertension,smoking and insulin therapy are additional risk factors.